2005
DOI: 10.1007/s11249-005-8313-z
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Films Formed by the Reaction of Carbon Tetrachloride with Iron

Abstract: The tribological properties of halide films grown on iron by reaction with carbon tetrachloride vapor at a temperature of 617 K and a pressure of 1.7 Torr are compared, in ultrahigh vacuum, with FeCl 2 films evaporated onto the surface. It is found that the reactively formed film has a slightly lower limiting friction coefficient than the evaporated layer ($0.06 compared to $0.08), which may be due either to the diffusion of some carbon into the substrate or the formation of a more oriented layer when this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Increasing the additive concentration results in an initially faster rate of ferrous chloride lm formation but, as soon as the interfacial temperature reaches the melting point of the lm material, the wear rate becomes asymptotically large and the lm is removed. This approach has also been used to explore the EP tribochemistry of other chlorine, 32,33,[46][47][48][49][50][51][52][53][54][55][56] sulphur, 57,58 and phosphorus-containing 59,60 lubricant additives.…”
Section: Extreme-pressure Tribochemistry Of Methylene Chloride On Ironmentioning
confidence: 99%
“…Increasing the additive concentration results in an initially faster rate of ferrous chloride lm formation but, as soon as the interfacial temperature reaches the melting point of the lm material, the wear rate becomes asymptotically large and the lm is removed. This approach has also been used to explore the EP tribochemistry of other chlorine, 32,33,[46][47][48][49][50][51][52][53][54][55][56] sulphur, 57,58 and phosphorus-containing 59,60 lubricant additives.…”
Section: Extreme-pressure Tribochemistry Of Methylene Chloride On Ironmentioning
confidence: 99%
“…Sulfur-containing molecules are also used as lubricant additives, where they react at the sliding interface to form friction- and/or wear-reducing films. , Early mechanistic work on sulfur-containing lubricant additives under so-called extreme-pressure (EP) conditions, where the interfacial temperatures were high (approaching ∼1000 K), revealed that the surface chemical processes that resulted in the formation of friction-reducing tribofilms were thermally driven. However, in the case of milder sliding conditions, where the temperature rise at the interface is negligible, the formation of a tribofilm can be driven by a mechanochemical process in which interfacial sliding lowers the reaction activation barrier, resulting in an acceleration of the reaction rate. In particular, this effect has been demonstrated for the gas-phase lubrication of copper by dialkyl disulfides (R–S–S–R, where R is an alkyl group). The dialkyl disulfides initially reacted rapidly on clean, well-characterized copper in ultrahigh vacuum (UHV) to form stable alkyl thiolate species. However, sliding on this surface induced the decomposition of the alkyl thiolate species to evolve gas-phase hydrocarbons and deposit sulfur on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The following investigates the surface chemistry of a borate ester, isopropoxy tetramethyl dioxaborolane (ITDB), on a Cu(111) surface to determine whether a reactive film can form near room temperature to potentially provide a tribofilm needed for lubrication of the sliding copper–copper contact in an electric motor. These experiments will provide the background information for eventually investigating the frictional properties in ultrahigh vacuum (UHV). ITDB contains both an alkoxy group and a bridging −O–C–C–O– group. The latter is included to improve the stability of ITDB toward reaction with water.…”
Section: Introductionmentioning
confidence: 99%